2005
DOI: 10.1088/0957-4484/16/9/046
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical properties of Au nanoparticles on indium–tin oxide substrate

Abstract: The nonlinear optical properties of gold nanoparticles with different densities of particles on indium–tin oxide (ITO) substrates of different origins are investigated. The coherent photoinduced nonlinear optical effect at 1.32 µm reveals a marked dependence on the interparticle distance and density. The decrease of the interparticle distance with the increase of Au nanoparticle density favours the photoinduced optical second harmonic generation. The maximal second-order optical susceptibility attained at a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 25 publications
0
54
0
Order By: Relevance
“…Formation of photoinduced phonons at the interface between the Au islands and the glass substrate can also contribute to the NLO response, emanating from photoinduced linear and nonlinear absorption, as has been discussed in the literature, [21] where the NLO properties of Au nanoparticles deposited on an indium tin oxide (ITO) substrate were investigated.…”
Section: Full Papermentioning
confidence: 99%
“…Formation of photoinduced phonons at the interface between the Au islands and the glass substrate can also contribute to the NLO response, emanating from photoinduced linear and nonlinear absorption, as has been discussed in the literature, [21] where the NLO properties of Au nanoparticles deposited on an indium tin oxide (ITO) substrate were investigated.…”
Section: Full Papermentioning
confidence: 99%
“…Due to the intense electromagnetic field located around the pods, star shape gold nanocrystals are highly SERS active, which makes these particles very attractive for various real life applications [6][7][8][9][10]. Recently we and other groups have shown that, due to the strong absorption in near IR, asymmetric nanoparticles are potential candidates for novel cancer therapeutic agents through photo-thermal mechanism [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the good progress over the past decade in the synthesis of gold nanomaterials of various sizes and shapes, an important challenge nanomaterials are facing in technological applications are due to the fact that the mechanisms underpinning these synthetic methods have evolved empirically and there is no accepted coherent mechanistic explanation to explain how shape control works [1][2][3][4][5][6]. The detailed understanding of the design and control parameters should have a profound impact on the engineering of the growth of nanoparticles to the desired size and shape, which is necessary for exploration of gold nanoparticles in a wide range of technological applications [6][7][8][9][10][11][12][13][14][15][16][17][18]. Usually nucleation and growth processes often occur on a relatively short time scales, as a result in situ timeresolved measurements are helpful to understand the growth mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations